2019
DOI: 10.1080/13880209.2019.1657906
|View full text |Cite
|
Sign up to set email alerts
|

Oxymatrine protects against l-arginine-induced acute pancreatitis and intestine injury involving Th1/Th17 cytokines and MAPK/NF-κB signalling

Abstract: Context: Oxymatrine (OMT) has various pharmacological effects, including immune reaction regulation, anti-inflammation and anti-hypersensitive reaction.Objective: This is the first report to investigate the molecular mechanism of OMT function in l-arginine (Arg)-induced acute pancreatitis (AP) involving intestinal injury.Materials and methods: Rat pancreatic AR42J and small intestinal IEC-6 cells were treated with Arg (200–800 µM) for 48 h plus OMT (4 mg/mL) treatment. Thirty adult Wistar rats were randomly as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…As IL-17 exacerbates AP through different mechanisms, pharmacological blockade of the gut microbiota may exert a partial effect on treating AP. Recent studies found that oxymatrine plays an anti-inflammatory role in AP intestinal injury by suppressing Th1/Th17 secretion of cytokines ( 137 ). Probiotics have protective functions against intestinal mucosal damage diseases.…”
Section: Therapeutic Implications Of Apmentioning
confidence: 99%
“…As IL-17 exacerbates AP through different mechanisms, pharmacological blockade of the gut microbiota may exert a partial effect on treating AP. Recent studies found that oxymatrine plays an anti-inflammatory role in AP intestinal injury by suppressing Th1/Th17 secretion of cytokines ( 137 ). Probiotics have protective functions against intestinal mucosal damage diseases.…”
Section: Therapeutic Implications Of Apmentioning
confidence: 99%
“…38,39 One group reported that OMT ameliorated l-arginine-induced acute pancreatitis and intestine injury through down-regulating MAPK/NF-κB activation. 40 In addition, OMT could prevent synovial inflammation by blocking the NF-κB pathway. 11 Hence, OMT may attenuate IVDD by suppressing NF-κB signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The MAPK cascade mediates diverse biological functions such as cell growth, adhesion, survival and differentiation through the regulation of transcription, translation, cytoskeletal rearrangements [26]. It had been reported that pancreatitis could be alleviated via reducing the production of TNF-α, IL-6, IL-1β which was associated with regulating the MAPK signaling way [27]. Xiang-Peng Zeng et al found that inhibiting the MAPK cascade including MAPK3 might be a potential anti-in ammatory strategy for pancreatitis [28].…”
Section: Discussionmentioning
confidence: 99%